Perspectives on Christian worship : 5 views : Ligon Duncan, Dan Kimball, Michael Lawrence & Mark Dever, Timothy Quill, Dan Wilt - Duncan, J. Ligon, 1960-; Kimball, Dan.; Lawrence, Michael; Dever, Mark.; Quill, Timothy C. J., 1949-; Wilt, Dan.; Pinson, J. Matthew, 1967- (Nashville, Tenn. : B & H Academic, 2009)
Perspectives on Christian Worship presents in counterpoint form five basic common beliefs on Christian worship that have developed over the course of church history with a view toward determining which is most faithful to Scripture. Each chapter is written by a prominent person within each tradition, and each writer has the opportunity to respond to each differing view. --from publisher description
Liturgical worship / Timothy C.J. Quill -- Responses to Timothy C.J. Quill -- Traditional evangelical worship / Ligon Duncan -- Responses to Ligon Duncan -- Contemporary worship / Dan Wilt -- Responses to Dan Wilt -- Blended worship / Michael Lawrence and Mark Dever -- Responses to Michael Lawrence and Mark Dever -- Emerging worship / Dan Kimball -- Responses to Dan Kimball.
Includes bibliographical references and indexes.
Keywords: Worship; Public worship